The role of physical education in shaping champion athletes’ character at PON: A literature study - Ridha, Sahbana; Warni, Herita (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Purpose: This research aims to analyze the role of physical education in character building of high-performing athletes through a literature study. As an essential component of the school curriculum, physical education has multidimensional contributions in developing values such as discipline, sportsmanship, cooperation, leadership, and fighting spirit, which are vital for athletic success. Methods: This study employs a descriptive-analytical method with content analysis techniques on relevant literature, particularly related to the National Sports Week (PON). Results: The findings indicate that physical education not only functions to enhance physical capabilities but also serves as an effective medium for athletes' character development. Conclusion: The study concludes that physical education plays a significant role in character formation of high-performing athletes, specifically in the context of PON, and emphasizes the importance of strengthening character-oriented physical education curriculum. This is expected to support the development of high-performing athletes while simultaneously shaping the nation's moral identity through sports. The practical implications of this research include collaboration among teachers, coaches, and policymakers to maximize the role of physical education in producing a generation of athletes with high integrity. This study also recommends further research to explore the implementation of character values across various educational levels and sports disciplines.